2020
DOI: 10.3390/diagnostics10070443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perspective and Translational Oncology of Liquid Biopsy

Abstract: The term liquid biopsy (LB) refers to the study of circulating tumor cells, circulating tumors nucleic acids free of cells or contained in exosomes, and information about platelets associated with tumors. LB can be performed in different biofluids and allows the limitations of tissue biopsy to be overcome offering possibilities of tumor identification reflecting in real time tumor heterogeneity. In addition, LB allows screening and early detection of cancer, real-time monitoring of therapy, stratificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 63 publications
0
35
0
3
Order By: Relevance
“…Liquid biopsy, as a non-invasive and developing tool, could solve many limitations faced with conventional biopsies ( Fernández-Lázaro et al, 2020 ). Studies have confirmed the promising roles of liquid biopsy in the clinical management of metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy, as a non-invasive and developing tool, could solve many limitations faced with conventional biopsies ( Fernández-Lázaro et al, 2020 ). Studies have confirmed the promising roles of liquid biopsy in the clinical management of metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…There are also several urine-based tests for detection of prostate cancer including SelectMDx (based on gene expression signature) and Progensa PCA3 (based on lncRNA expression signature) [ 170 , 171 ]. Both tests revealed their potential in elimination of unnecessary prostate biopsies [ 172 ].…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%
“…In addition, the isolation of a specific EVs population released by pathogenic cells seems of great interest in the screening of people considered under risk of development of particular diseases [ 28 , 29 ]. Moreover, the feasibility of the isolation of a specific exosomes or vesicles population opens the opportunity to set up effective liquid biopsy approaches, in order to reduce invasive and painful conventional tissue biopsies [ 30 , 31 , 32 ]—in particular for the very challenging anatomical districts such as the brain [ 33 , 34 ]. In fact, in diseases affecting the central nervous system, neurologists have no access to the diseased tissue, with the exception of extreme cases requiring a cerebral biopsy.…”
Section: Evs As Biomarkersmentioning
confidence: 99%